Análise arquetípica do padrão relacional dos elementos do Design em revistas digitais - Raposo, João Rocha (2014)
The digital platform brought a new form of narrative in the communication field. Therefore, a reading relationship emerges. It was before based on a static visual and textual content and became innovative ways of the digital magazines universe, characterized by the incorporation of dynamic elements such as audio, video and interactive infographics. The connection with the reader is multiplied in a multisensory experience that unites the vision, hearing, and the unprecedented tactile experience of handling information on touch screens of mobile devices. On this approach, the digital magazine reaches diverse audiences that can be separated by different editorial proposals, defining the magazine profile. The graphical design elements are important to shape the editorial identity. In this alignment, the study attempts to identify the relational pattern of the design elements and how they contribute to the construction of the visual identity in digital magazines. The operationalization of the specific objectives adopted was the methodological approach of qualitative research, with exploratory and descriptive-analytical character and theoretical and practical basis. For the record: 1) conceptual dialogue between Design and the Jungian Symbolic Pedagogy, featuring the interdisciplinary proposal; 2) selection of the digital magazines; 3) case study based on the description of design elements in digital consumer magazines, study scope; 4) archetypal analysis to identify the relational pattern of the graphic elements in the design composition of digital consumer magazines; and, 5) considerations of the analysis about the objects of the searched unit. As a conclusion of this thesis, it is deduced that the relational pattern of the design elements in digital consumer magazines, limited to this research, presents an editorial profile that adheres to the characteristics of matriarchal, patriarchal and otherness archetypal patterns. As a contribution, the interdisciplinarity undertaken allows to unveil the windows of possibilities for future researches, incorporating new concepts and new relationships between graphical elements and archetypal patterns, enabling the expansion of the theoretical and practical basis in the Design area.